A novel staphylococcal enterotoxin SE02 involved in a staphylococcal food poisoning outbreak that occurred in Tokyo in 2004. (December 2020) - Suzuki, Yasunori; Ono, Hisaya K.; Shimojima, Yukako; Kubota, Hiroaki; Kato, Rei; Kakuda, Tsutomu; Hirose, Shouhei; Hu, Dong-Liang; Nakane, Akio; Takai, Shinji; Sadamasu, Kenji
Abstract: Staphylococcal enterotoxins (SEs) are extracellular proteins, produced mainly by Staphylococcus aureus, which cause staphylococcal food poisoning (SFP) when ingested. Here, a novel SE was identified from two strains, which were identified as the causative microbes of the SFP outbreak that occurred in Tokyo in 2004. Both strains harbored the SEA gene, but its production was lower than that of other SEA-producing SFP isolates. Whole-genome sequencing analysis demonstrated that both strains harbored a SE-like gene besides sea . Phylogenetic analysis revealed that the amino acid sequence deduced from the SE-like gene belonged to the SEB group. Therefore, this gene was presumed to be a novel SE gene and termed "SE02." The stability of SE02 against heating and proteolytic digestions was a little different from that of SEA. SE02 has both superantigenic and emetic bioactivities. Namely, SE02 activated mouse splenocytes and exhibited emetic activity in the common marmoset. SE02 mRNA was highly expressed in both isolates during the exponential phase of cultivation. In addition, SE02 protein was produced at 20 °C and 25 °C, which reflects the actual situation of SFP. SE02 appears to be a novel emetic toxin that was likely the causative toxin in combination with SEA in the SFP outbreak. Highlights: A novel SE, SE02, was identified from low-SEA-producing SFP isolates. SE02 had two SE-specific bioactivities, emetic and superantigenic. SE02 was resistant to heating and pepsin digestion to a certain degree. SE02 was produced at room temperature, which reflects the setting of SFP. SE02 was likely the causative toxin in combination with SEA in the SFP outbreak.